Serum omentin-1 as a predictor of activity in Crohn's disease - Mohammed A Mohammed; Nesreen M Omar (SpringerOpen, 2019)
Background and aim Crohn's disease (CD) is associated with alterations in fat mass and fat distributions, with changed productions of adipokines, including omentin-1. Omentin-1 may be involved in the pathogenesis of inflammatory bowel disease. The aim was to determine the serum and mucosal omentin-1 levels in CD patients and to evaluate its potential as a marker for disease activity. Patients and methods Seventy-five adult consecutive outpatients, with a confirmed diagnosis of CD, and 45 age-matched, sex-matched, and BMI-matched healthy volunteers were enrolled in this study after written conscious consent and approval by the Institutional Review Board of Mansoura University. CD was diagnosed by conventional clinical, radiological, endoscopic, and histopathological criteria. Serum levels and mucosal mRNA expression of omentin-1 were measured by commercially available kits according to the manufacturer's protocols. Results Serum omentin-1 and its mucosal gene expression were significantly lower in patients with CD (53.3±12.8) than in healthy controls (72.7±16.8, P˂0.0001). Moreover, serum omentin-1 levels were significantly lower in patients with active CD (36.2±9.6) than in patients in remission (69.2±14.4, P≤0.0001). No significant differences were demonstrated between patients in remission and healthy controls (P>0.05). In CD patients, the decrease in serum omentin-1 was associated with a significantly higher BMI, C-reactive protein, erythrocyte sedimentation rate, Crohn's disease activity index, simplified endoscopic score for CD and inflammation scores (P≤0.05). Moreover, omentin-1 was much superior to C-reactive protein in predicting CD activity and severity. Conclusion Serum and mucosal expression of omentin-1 might be a reliable surrogate noninvasive marker of disease activity in CD with significantly high sensitivity, specificity, and diagnostic accuracy.